Eksperimentasi Model Pembelajaran Quantum Learning Berbasis Pendekatan Scientific Terhadap Hasil Belajar Siswa pada Pokok Bahasan Puisi - Imam Kisnanto; Muhamad Sholehhudin; Joko Setiyono (Universitas Ahmad Dahlan, 2019)
This research aims to determine whether the Quantum Learning model based on the Scientific approach can provide better learning outcomes rather than direct learning model. This research is a quasi experimental research with matching static group comparison design. The research instrument used to obtain data is in the form of documentation and test. The calculation of the hypothesis test the value of tcount > ttable where tcount = 1.83 and ttable = 1.68 at the significant level of 5% with dk=50. The conclusions from the analysis of the hypothesis test is that the Quantum Learning model based on Scientific approach provides better learning outcomes than students who were taught using direct learning models.